Academic Interest in COVID-19 - Geroğlu, Berk (Turkey Health Literacy Journal, 2020)
COVID-19 is a disease that first appeared in Wuhan, China in late December 2019, causing symptoms such as fever, cough, and shortness of breath. The name of the virus that causes COVID-19 is SARS-CoV-2. On March 10, 2020, one day after the first case seen in Turkey, the World Health Organization declared COVID-19 as a pandemic on March 11, 2020. As the number of COVID-19 cases continue to increase rapidly all over the world, the number of scientific publications on COVID-19 has increased day by day.
Keywords: COVID-19; coronavirus; academic